f(n) = f(n+1) +3
f(1) = f(2) +3
f(2) =f(3) +3
f(3) = f(4) +3
So f(1) = f(n) + 3* (n-1)
Put n=4 here so you found
f(1) = f(4) + 3* 3
= 22 +9
=31 ans
hope it helps
Step-by-step explanation:
ABC is an isoceles triangle (both legs are equally long). and AB is its baseline.
OC is now a median for ABC splitting the angle at C and AB in half.
so, we have 2 right-angled triangles : OAC and OBC.
the half-angles at C are 42/2 = 21°.
the angles at A and B are 90°.
and the half-angles at O are 180 - 90 - 21 = 69°.
remember that the sum of all angles in a triangle must always be 180°.
AB are the heights of both of these triangles.
the single height is sin(69)×7 = 6.535062985... cm
and so,
AB = 2× height = 13.07012597... cm.
9514 1404 393
Answer:
(c) P(x) = x^4 +3x^3 -10x^2 -30x
Step-by-step explanation:
If the polynomial has integer coefficients, its complex or radical roots come in conjugate pairs. That is, -√10 is also a root. The four roots mean the polynomial has degree 4. That eliminates all but answer choice C.
Each root 'a' gives rise to a factor (x -a), so the factored polynomial is ...
P(x) = (x -0)(x -(-3))(x -√10)(x -(-√10))
P(x) = x(x +3)(x² -10) = x(x³ +3x² -10x -10)
P(x) = x^4 +3x^3 -10x^2 -10x
Expressed a proper fraction in its simplest form, 0.79 is equal to 79/100, or this seventy-nine hundredths
Answer:
(400/100)*80 = 320
Step-by-step explanation:
400 = 100%, just divide by 100 and multiply by 80